Pengaruh Pendidikan Agama Islam Terhadap Kesadaran Beribadah Siswa Kelas IX MTs Miftahul Ulum Pronojiwo Lumajang - Rohmah, Intan Muthi'atur; Nursyamsiyah, Siti; Tamami, Badrut (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) STIB Banyuwangi, 2025)
Awareness of worship is an important aspect of a Muslim's life which is ideally formed from the age of adolescence through a systematic process of religious education. However, in reality, there are still students who have not shown consistency in carrying out worship, especially praying five times, even though they have received formal religious learning. This research aims to examine the effect of Islamic Religious Education on the worship awareness of ninth-grade students at MTs Miftahul Ulum Pronojiwo, Lumajang. A quantitative method was employed, utilizing survey techniques and data analysis through simple linear regression. The study involved the entire population of ninth-grade students, totaling 42 individuals, all of whom were included as research subjects using a total sampling method. The data collection instrument was a questionnaire based on a Likert scale, incorporating indicators related to religious education and worship awareness. The findings indicate a significant relationship between Islamic Religious Education and students’ level of worship awareness. This proves that religious learning in schools, if carried out effectively and contextually, can increase students' understanding, motivation, and consistency in carrying out worship. This research provides important implications for the development of a more grounded and applicable PAI curriculum and teaching methods in shaping students' spiritual character.